Comparison of serum tryptase as a diagnostic oncological marker in canine versus human mast cell neoplasms. (10th December 2022) - De Vos, Shana; Demeyere, Kristel; De Cock, Hilde; Devriendt, Nausikaa; Schwarzkopf, Ilona; Fortrie, Ruth; Roggeman, Tom; Meyer, Evelyne; De Spiegelaere, Ward; de Rooster, Hilde
Abstract: Canine mast cell tumors (MCTs) are a promising translational model for human mast cell neoplasms with striking similarities such as the Darier's sign and mutations in the KIT gene. Whereas mast cell neoplasms are rare in humans, MCTs are the most frequent malignant neoplasms of the skin in dogs. In human systemic mastocytosis, serum tryptase is an important diagnostic criterion. Surprisingly, serum tryptase levels were not yet investigated in dogs with MCTs. Therefore, the aim of this study was to investigate whether serum tryptase levels in dogs with cutaneous MCTs were elevated compared to those of a non-MCT control group. As a secondary aim, it was investigated whether surgical manipulation caused an increase in serum tryptase in canine MCT patients. A total of 48 serum samples were collected from dogs with different grades of cutaneous MCTs (n = 24) and non-MCT controls (n = 24). In dogs with cutaneous MCTs, blood was collected prior to and within 1 h after surgery. Serum tryptase levels were measured using a commercially available canine-specific ELISA kit. No significant difference in serum tryptase levels was found between cutaneous MCT patients and non-MCT controls, nor in these levels before versus after surgery. Our findings in canine cutaneous MCTs are in accordance with human cutaneous mastocytosis, where serum tryptase levels tend to remain within the normal range. However, despite various similarities between aggressive mast cell tumors in dogs and humans, serum tryptase cannot be considered a diagnostic biomarker in dogs with cutaneous MCTs as part of a comparative oncologic strategy.